2021
DOI: 10.1038/s41467-021-23434-z
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of Plasmodium falciparum transmission through the mosquito

Abstract: Malaria parasites have a complex life cycle featuring diverse developmental strategies, each uniquely adapted to navigate specific host environments. Here we use single-cell transcriptomics to illuminate gene usage across the transmission cycle of the most virulent agent of human malaria - Plasmodium falciparum. We reveal developmental trajectories associated with the colonization of the mosquito midgut and salivary glands and elucidate the transcriptional signatures of each transmissible stage. Additionally, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 81 publications
11
72
0
Order By: Relevance
“…Single-cell RNA-sequencing (scRNA-seq) methods offer new ways of studying cell-to-cell variation (Aldridge and Teichmann, 2020), and have already allowed for novel insights into host-pathogen interactions in various disease contexts (Penaranda and Hung, 2019). In Plasmodium spp., scRNA-seq analyses have so far revealed that individual parasite forms exist on a spectrum of transcriptomic states (Bogale et al, 2021; Howick et al, 2019; Poran et al, 2017; Real et al, 2021; Reid et al, 2018; Ruberto et al, 2021a), and applying them to study the biology of P. vivax is a burgeoning area of research (Mancio-Silva et al, 2021; Ruberto et al, 2021b; Sà et al, 2020). Droplet-based techniques, such as 10x Genomics (Zheng et al, 2017), which use microfluidics, allow for the sequencing of tens to hundreds of thousands of cells, increasing the chances of observing rare cell populations (e.g., hepatocytes infected with P. vivax ).…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell RNA-sequencing (scRNA-seq) methods offer new ways of studying cell-to-cell variation (Aldridge and Teichmann, 2020), and have already allowed for novel insights into host-pathogen interactions in various disease contexts (Penaranda and Hung, 2019). In Plasmodium spp., scRNA-seq analyses have so far revealed that individual parasite forms exist on a spectrum of transcriptomic states (Bogale et al, 2021; Howick et al, 2019; Poran et al, 2017; Real et al, 2021; Reid et al, 2018; Ruberto et al, 2021a), and applying them to study the biology of P. vivax is a burgeoning area of research (Mancio-Silva et al, 2021; Ruberto et al, 2021b; Sà et al, 2020). Droplet-based techniques, such as 10x Genomics (Zheng et al, 2017), which use microfluidics, allow for the sequencing of tens to hundreds of thousands of cells, increasing the chances of observing rare cell populations (e.g., hepatocytes infected with P. vivax ).…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell RNAseq opens the door to study heterogenous populations of single-celled parasites by delineating expression patterns of individual cells allowing us to understand continuous developmental processes, cell-type specific patterns of co-expression and bet-hedging strategies [11][12][13][14][15][16][17]. Recent studies have profiled T. brucei populations using single-cell dropletbased approaches from BSF culture to profile the development of stumpy forms [18] as well as in vivo salivary gland parasites in order to identify a potential vaccine candidate among mature…”
Section: Introductionmentioning
confidence: 99%
“…In Plasmodium species, scRNA-seq has been used to describe cell populations through the entire life cycle, from the IDC through the mosquito (38)(39)(40)(41)(42)(43)(44)(45). This has led to the development of comprehensive cell atlases for both P. berghei (39) and P. falciparum (46). Additionally, scRNA-seq in T. gondii was used to reveal novel regulators of life cycle stage progression (47,48).…”
Section: Introductionmentioning
confidence: 99%